Peran Komunikasi Interpersonal Antara Mahasiswa Etnik Cina dan Batak Toba Dalam Akulturasi Budaya di Universitas Prima Kota Medan - Annisa, Annisa; Matondang, Armansyah (Universitas Medan Area, 2025)
This study aims to analyze the role of interpersonal communication in the process of cultural acculturation between ethnic Chinese and Batak Toba students at Prima University, Medan. In Indonesia, which is rich in cultural diversity, intercultural communication is the key to building harmonious relationships in a multicultural campus environment. Through a qualitative approach and case studies, data were collected through in-depth interviews and observations of five students from both ethnicities. The results of the study show that open, empathetic, and respectful interpersonal communication plays an important role in reducing prejudice and facilitating interaction between students. Social activities, group discussions, and campus cultural events are the main means of exchanging values and learning about each other's cultures. Despite challenges such as stereotypes, prejudices, and language barriers, the use of social media plays a significant role in strengthening communication between students, allowing them to share cultural experiences more broadly. This study suggests that universities should continue to support activities that encourage intercultural interaction and strengthen interpersonal communication among students.